Biomarker responses and PAH ratios in fish inhabiting an estuarine urban waterway - Duarte, R.; Sadauskas-Henrique, H.; de Almeida-Val, V.; Val, A.; Nice, H.; Gagnon, Marthe Monique (John Wiley and Sons, 2017)
© 2017 Wiley Periodicals, Inc. Many cities worldwide are established adjacent to estuaries and their catchments resulting in estuarine contamination due to intense anthropogenic activities. The aim of this study was to evaluate if fish living in an estuarine urban waterway were affected by contamination, via the measurement of a suite of biomarkers of fish health. Black bream (Acanthopagrus butcheri) were sampled in a small urban embayment and a suite of biomarkers of fish health measured. These were condition factor (CF), liver somatic index (LSI), gonadosomatic index (GSI), hepatic EROD activity, polycyclic aromatic hydrocarbon (PAH) biliary metabolites, serum sorbitol dehydrogenase (s-SDH) and branchial enzymes cytochrome C oxidase (CCO), and lactate dehydrogenase (LDH) activities. The biomarkers of exposure EROD activity, and pyrene- and B(a)P-type biliary metabolites confirmed current or recent exposure of the fish and that fish were metabolizing contaminants. Relative to a reference site, LSI was higher in fish collected in the urban inlet as was the metabolic enzyme LDH activity. CF, GSI, s-SDH, CCO, and naphthalene-type metabolites were at similar levels in the urban inlet relative to the reference site. PAH biliary metabolite ratios of high-molecular-weight to low-molecular-weight suggest that fish from the urban inlet were exposed to pyrogenic PAHs, likely from legacy contamination and road runoff entering the embayment. Similarly, the sediment PAH ratios and the freshness indices suggested legacy contamination of a pyrogenic source, likely originating from the adjacent historic gasworks site and a degree of contamination of petrogenic nature entering the inlet via storm water discharge. Biomarkers of exposure and effect confirmed that black bream collected in the Claisebrook Cove inlet, Western Australia, are currently exposed to contamination and are experiencing metabolic perturbations not observed in fish collected at a nearby reference site.